Kansas PRIDE 2011 Annual Review - Kahl, Dan; Rice, Trudy; Menon, Jaime (My University, 2011)
Summary of the 2011 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development